PENGARUH BEBAN KERJA, LINGKUNGAN KERJA DAN KOMITMEN TERHADAP KINERJA PEGAWAI PADA BIDANG KEPEGAWAIAN LEMBAGA PEMASYARAKATAN KELAS IIA YOGYAKARTA - Subiyantoro, Ary; Rahmatia, Reska (Kajian Ekonomi dan Bisnis, 2024)
This writing aims to find out how workload, work environment and commitment influence employee performance in the staffing sector at class IIa Yogyakarta correctional institutions. Data analysis techniques use validity tests, reliability tests, multiple regression analysis, f tests and t tests. Based on the research results, the multiple regression equation Y = -3.736 + 0.371X1 + 0.233X2 + 0.455X3 shows that there is an influence between workload, work environment and commitment on employee performance in the staffing sector at the Yogyakarta class IIa Correctional Institution. From the results of the coefficient of determination test, it shows that the R Square is 0.836. This means that the magnitude of the influence of workload, work environment and commitment variables on employee performance in the staffing sector at Yogyakarta class IIa correctional institutions is 83.6%, while the remaining 16.4% must be explained by other causal factors originating from outside the regression method. This.